2012
DOI: 10.3389/fonc.2012.00176
|View full text |Cite
|
Sign up to set email alerts
|

Repair of 3-methyladenine and abasic sites by base excision repair mediates glioblastoma resistance to temozolomide

Abstract: Alkylating agents have long played a central role in the adjuvant therapy of glioblastoma (GBM). More recently, inclusion of temozolomide (TMZ), an orally administered methylating agent with low systemic toxicity, during and after radiotherapy has markedly improved survival. Extensive in vitro and in vivo evidence has shown that TMZ-induced O6-methylguanine (O6-meG) mediates GBM cell killing. Moreover, low or absent expression of O6-methylguanine-DNA methyltransferase (MGMT), the sole human repair protein that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
72
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 41 publications
(74 citation statements)
references
References 61 publications
0
72
0
Order By: Relevance
“…Previous studies have suggested that MGMT and base excision repair (BER) are involved in TMZ resistance [15, 16]. MGMT also repairs the O 6 -chloroethylguanine residues induced by SN2-type methylating agents such as ACNU [17, 18].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have suggested that MGMT and base excision repair (BER) are involved in TMZ resistance [15, 16]. MGMT also repairs the O 6 -chloroethylguanine residues induced by SN2-type methylating agents such as ACNU [17, 18].…”
Section: Discussionmentioning
confidence: 99%
“…In the context of chemotherapy employing DNA‐alkylating drugs (e.g., methyl methanesulfonate (MMS) or temozolomide), the major DNA alkylation product, N 7 ‐methylguanine, undergoes spontaneous depurination, leading to formation of AP sites, as well as a reaction with histone proteins, leading to the generation of DNA–protein cross‐links . Whereas the latter are thought to be cytotoxic, AP sites are instantly processed by the base‐excision DNA repair (BER) pathway, which eliminates drug‐induced DNA damage and leads to chemoresistance . It has been demonstrated that inhibition of BER increases the sensitivity of cancer cells towards DNA‐alkylating drugs in certain cancers, leading to a therapeutically useful synergic effect .…”
Section: Introductionmentioning
confidence: 99%
“…Major DNA adducts generated by TMZ are N 7 ‐methylguanine (N 7 ‐MeG; 60‐80%), N 3 ‐methyladenine (N 3 ‐MeA; 10–20%), and O 6 ‐methylguanine ( O 6 ‐MeG; 5–10%) (Bobola et al ., 2012). Excision of a modified base generates an apurinic/apyrimidinic (AP) DNA site, and consecutive AP endonuclease 1 (APE1) activity creates a single‐stranded DNA site which has the propensity to develop into a double‐strand break if not processed expediently by BER (Helena et al ., 2018).…”
Section: Discussionmentioning
confidence: 99%
“…We therefore focused on N 7 ‐MeG and N 3 ‐MeA adducts which constitute over 90% of TMZ‐induced base alterations. These are recognized by the BER glycosylase MPG which performs the initial cleavage of the glycosylic bond between the damaged base and deoxyribose to generate an AP site (Bobola et al ., 2012; Kim and Wilson, 2012). Treatment of human GBM cells with RXFP1 agonist CTRP8 increased MPG protein levels and MPG activity as determined by MPG molecular beacon assay, while the cellular levels of other BER proteins, including APE1, DNA polymerase ÎČ (polÎČ), and XRCC1, remained unaffected by CTRP8‐mediated RXFP1 activation.…”
Section: Discussionmentioning
confidence: 99%